Enhancing Digital Literacy for Rural Communities in Empat Negeri Village, Batu Bara Regency - Nasution, Mira Nazwa Utami; Aqilah, Najla; Atfa, Raudhatun; Nasution, Insya Widya Agustini; Sopha, Diana (Raskha Media Group, 2025)
This community service initiative was designed to enhance the technological capacity and digital awareness of residents in Empat Negeri Village, Batu Bara Regency. The community initially faced difficulties in utilizing digital media effectively for learning, communication, and local economic activities. The primary aim of this program was to develop essential digital competencies that would foster independence and long-term community resilience. Implementation involved interactive outreach, practical workshops, and guided digital exercises facilitated by one lecturer and four students from the University of Muslim Nusantara Al Washliyah, working collaboratively with village authorities. The activity involved around 50 participants, consisting of small business owners, youth, and local community figures. The evaluation process included preliminary and final assessments, observational notes, and reflection sessions to measure learning progress and engagement. The outcomes demonstrated a notable increase in digital skills, as participants displayed greater proficiency and confidence in operating computers, smartphones, and digital platforms. The overall digital literacy rate rose from 25% before training to approximately 75% afterward. Several participants were able to apply digital tools in promoting their businesses and accessing online learning opportunities. This initiative successfully strengthened rural communities’ readiness for the digital era, while fostering educational equity and economic participation.